An Integrated Approaches in Teaching Foreign Language - Mamedova Madina Ashuralievna; Mekhriniso Muradulloyevna Amonova (Genius Journals, 2023)
This article discusses the role of foreign languages in the world and analyzes the benefits of using an integrated approach to foreign language teaching. Especially in classes learning English as a foreign language, one can get a lot of information on the methodology of teaching interdisciplinary relations through various opinions, discussions and articles on the integrated approaches in teaching languages.
Keywords: integrative approach; foreign language; teaching process